Moving on from crime and substance use: transforming identities - Robinson, Anne; Hamilton, Paula (Policy Press, 2016)
As 'offenders' turn their backs on crime, they often change their identities as well as their behaviour, yet we know much less about how reforming identity might be affected by gender, age or ethnicity. This book showcases research from a wide range of authors in the field. It considers the similarities and differences between desisting from crime and recovering from addiction. Taking the desistance and recovery debates in unfamiliar directions, it examines the experiences of change for individuals seeking healthier and more successful futures